Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006520.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapies for hypochondriasis

Abstract: Cognitive therapy, behavioural therapy, cognitive behavioural therapy and behavioural stress management are effective in reducing symptoms of hypochondriasis. However, studies included in the review used small numbers of participants and do not allow estimation of effect size, comparison between different types of psychotherapy or whether people are "cured". Most long-term outcome data were uncontrolled. Further studies should make use of validated rating scales, assess treatment acceptability and effect on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 64 publications
5
74
0
Order By: Relevance
“…Additionally, hypochondriasis is more common in patients with psychiatric disorders, especially depression [13]. This underlying fear of illness may trigger a ''pain alarm,'' thus leading to both higher levels of attention by healthcare professionals and an increased use of resources [38]. In other words, depressed and anxious inpatients may feel less well for a given pathophysiology-ie, they may have less disease than the average inpatient with a similar illness.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hypochondriasis is more common in patients with psychiatric disorders, especially depression [13]. This underlying fear of illness may trigger a ''pain alarm,'' thus leading to both higher levels of attention by healthcare professionals and an increased use of resources [38]. In other words, depressed and anxious inpatients may feel less well for a given pathophysiology-ie, they may have less disease than the average inpatient with a similar illness.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological treatment is not normally acceptable to patients, as those with marked health anxiety are typically very sensitive to adverse effects of medication: but fluoxetine showed some benefit over placebo, though this was not pronounced and occurred late in treatment (8-12 weeks [I (PCT)] (Fallon et al, 2008). Psychological treatments have been found beneficial [I (M)] ( Thomson and Page, 2007), and include behavioural stress management (Clark et al, 1998) ([II]), cognitive behaviour therapy, in both face-to-face and internet format (Hedman et al, 2011b;Seivewright et al, 2008;Sørensen et al, 2011) (Tyrer et al, 2014).…”
Section: Marked Health Anxiety ('Illness Anxiety Disorder')mentioning
confidence: 99%
“…Health anxiety is defined as anxiety about a health condition that only responds temporarily, if at all, to reassurance and is associated with some insight. Normal investigations may have the paradoxical effect of worsening the condition-there must be something if they need to do a scan they just haven t found it, yet A Cochrane review concluded that psychotherapy for health anxiety in general (hypochondriasis) showed significant improvement on average across studies [22]. When identified treatment of health anxiety is therefore often clinically rewarding.…”
Section: Health Anxiety About Dementiamentioning
confidence: 99%